Nonylphenol reduces sperm viability and fertility of mature male breeders in Brown Tsaiya ducks (Anas platyrhynchos) - Cheng, Min-Chien; Chiang, Hsin-I.; Liao, Jiunn-Wang; Hung, Che-Ming; Tsai, Ming-Yang; Chen, Yu-Hsin; Ju, Jyh-Cherng; Cheng, Mei-Ping; Tso, Ko-Hua; Fan, Yang-Kwang (Animal reproduction science, 2016)
The aim of this study was to investigate the effect of nonylphenol (NP), a widely used surfactant, on the reproductive performance of male Brown Tsaiya ducks (Anas platyrhynchos) (MBBTDs). Mature MBBTDs (n=100) were treated with NP by daily gavaging of 0, 1 (NP1), 10 (NP10) and 250 (NP250) mg/kg-BW/d for 14 wk. Semen quality, fertilization rate and specific factors in blood plasma were measured. Weights of organs were also measured at 14 wk after NP administration. Ducks from each treatment (n=4) were continually treated with NP thereafter for 12 mo to observe changes of tissue ultrastructure by microscopic examination. The results showed that ducks treated with amounts of NP of greater than 1mg NP/kg BW/d (NP1) for 14 wk had decreased sperm viability (32.3%) compared to those in the control group (74.1%, P<0.05). The fertilization rate of ducks treated with 250mg NP/kg-BW/d (NP250) for 14 wk was reduced (21.0%) compared to the control group (74.5%, P<0.05). Plasma aminotransferase (AST) and alanine aminotransferase (ALT) activities were also greater in NP250 group at the 14th wk post-treatment. Plasma testosterone concentrations were increased by NP1 treatment at the 14th wk post-treatment. Administration at dosage 250mg NP/kg-BW/d for 12 mo resulted in reduced sperm counts (P<0.05) and histopathological changes, such as dilated seminiferous tubules (P<0.05) and degenerated spermatocytes (P<0.05). These findings strongly suggest that NP adversely affects the reproductive performance of MBBTDs.